Morphological comparison of spermatozoa taken from TESE and PESA specimens in infertile men who referred to the infertility sections of Shariati Hospital and Navid Clinic in 1378 - H Saeidi Saeidabady; A Alyasin; M Agha Hossinei; A Khademi; H Sahebkashaf; S Sahebkashaf; O Poyan (JRI, 2000)
In this study morphology of testicular and epididymal sperm was assessed. Morphology of sperms was assessed by using Tygerbery strict criteria. TESE and PESA were done by conventional method under local anesthesia.Percentages of normal and abnormal sperm was studied. The percentage of normal testicular sperm ( 6.2% ) differed significantly from the percentage of normal epididymal sperm (18.6%). Percentages of abnormal form of head and tail differs in two groups but Percentage of midpiece abmormalities were not significantly different between the two groups.To assess the predictive value of Tygerberg strict criteria for determining morphology of testicular sperms we need a healthy control group.
Keywords: Morphology, Sperm, PESA, Testicular sperm extraction